Religious Architecture Anthropological Perspectives - Verkaaik, Oskar (Amsterdam University Press, 2013)
Religious Architecture: Anthropological Perspectives develops an anthropological perspective on modern religious architecture, including mosques, churches and synagogues. Borrowing from a range of theoretical perspectives on space-making and material religion, this volume looks at how religious buildings take their place in opposition to the secular surroundings, how they, as evocations of the sublime, help believers to move beyond the boundaries of modern subjectivity, and how they, in their common sense definition, function as community centers in urban daily life. The volume includes contributions from a range of anthropologists working in the UK, Mali, Brazil, Spain and Italy.